Digital Connectedness and Exports Upgrading: Is Sub-Saharan Africa Catching Up? - (:unkn) unknown (My University, 2023)
We highlight a new dimension of the submarine cable infrastructure network, termed 'digital connectedness', reflecting a country's digital proximity to main world markets, and assess its impact on export upgrading. Using an instrumental variables approach conducted on a sample of 60 developing countries-including 23 sub-Saharan African countries-over the period 1995-2017, we find that digital connectedness contributes positively and significantly to the export basket complexity, but also points out spatial heterogeneity within our sample. In fact, estimations stress that, compared to the Rest of the World, a 10pp increase in the share of world GDP directly cabled to SSA countries leads to a supplementary increase ranging from 4.6 index points to 5.3 index points in the export complexity index. Moreover, while everywhere else the positive effect of digital connectedness declines with distance from global markets, in Sub-Saharan Africa the benefit increases. Finally, in line with the literature, improved digital connectedness also translates into higher exports of differentiated goods and greater participation in the global value chain.
Keywords: African Research